Comparison of C-Reactive Protein and Low-Density Lipoprotein Cholesterol Levels in the Prediction of First Cardiovascular Events - Ridker, Paul M; Rifai, Nader; Rose, Lynda; Buring, Julie E; Cook, Nancy R (The New England journal of medicine, 2002)
Studies have suggested that C-reactive protein, a marker of inflammation, may predict the risk of cardiovascular events, including coronary events. In this study of nearly 28,000 women, C-reactive protein levels were found to predict the risk of subsequent cardiovascular events independently of other known coronary risk factors. C-reactive protein and low-density lipoprotein cholesterol levels were found to be complementary in the prediction of risk. C-reactive protein levels predict the risk independently of other risk factors. Because of its critical importance in atherogenesis, low-density lipoprotein (LDL) cholesterol is the focus of current guidelines for the determination of the risk of cardiovascular disease. 1 However, atherothrombosis often occurs in the absence of hyperlipidemia, and recent consensus panels assembled by the National Heart, Lung, and Blood Institute and the Centers for Disease Control and Prevention have concluded that population-based data on other risk factors are urgently needed. 2 , 3 Among the biologic markers considered by those panels, there was particular interest in C-reactive protein, a marker of inflammation that has been shown in several prospective, nested case–control studies to be . . .